Experimental Study on the Impact of NaCl Concentration on the Flocculating Settling of Fine Sediment in Static Water. (2016) - Ou, Yangming; Li, Ran; Liang, Ruifeng
Abstract: NaCl concentration can increase the flocculation of the fine-grained sediments in suspension. However, the impact of NaCl concentration on the process of flocculation and settling is unclear. This paper investigated the effect of NaCl concentration on the settling velocity of fine sediments, which kaolin is the constituent mineral of the sediment sample ( D 10 =0.9  μm ; D 50 =2.7  μm ; D 90 =10.3  μm ). The experiments were conducted in a 1.2 meter high settling column. Experimental cases were set for different initial concentration of sediment (0.2, 0.5, 1.0 g·l -1 ) and different NaCl concentration (0, 0.2, 0.5, 1.0, 2.0 g·l -1 ). With respect to each case, water samples were collected and measured at 11 different times from 0 min to 300 min during the process of experiment. Settling velocities were calculated based on the time evolution of suspended sediment concentrations. The experimental results show the time evolution of the relative sediment concentration, which is the ratio of the concentration to the initial concentration, follows a hyperbolic dynamic model under the low initial sediment concentration conditions. The settling velocity increases with the NaCl concentration and sediment concentration. An empirical formula among the settling velocity of sediment, salinity and sediment concentration have been established by means of the multiple linear regression analysis.